2011
DOI: 10.1182/blood-2011-06-361618
|View full text |Cite
|
Sign up to set email alerts
|

Intensive strategy to prevent CMV disease in seropositive umbilical cord blood transplant recipients

Abstract: Seropositive umbilical cord blood transplant (UCBT) recipients are at increased risk for CMV complications. To reduce CMV complications, we adopted an intensive strategy that consisted of ganciclovir administered before transplantation (5 mg/kg intravenously daily from day ؊8 to day ؊2), high-dose acyclovir (2 g, 3 times daily) after transplantation, and biweekly monitoring with a serum CMV PCR for preemptive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 48 publications
7
80
0
Order By: Relevance
“…Saavedra S [34] reported that all of their patients (100%) experienced at least 1 infectious episode, and 66% of them suffered from severe infections. Bloodstream infections occurred in 10% of the patients in our study, and the rate of CMV reactivation in the overall series was 56.7% (17 of 30), which was similar to the reports in the literature [35,36], but the number of CMV-DNA copies decreased significantly compared to that in other reports. None of the patients developed CMV disease, whereas Milano F [36] reported an incidence of CMV disease of 5-28%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Saavedra S [34] reported that all of their patients (100%) experienced at least 1 infectious episode, and 66% of them suffered from severe infections. Bloodstream infections occurred in 10% of the patients in our study, and the rate of CMV reactivation in the overall series was 56.7% (17 of 30), which was similar to the reports in the literature [35,36], but the number of CMV-DNA copies decreased significantly compared to that in other reports. None of the patients developed CMV disease, whereas Milano F [36] reported an incidence of CMV disease of 5-28%.…”
Section: Discussionsupporting
confidence: 90%
“…Bloodstream infections occurred in 10% of the patients in our study, and the rate of CMV reactivation in the overall series was 56.7% (17 of 30), which was similar to the reports in the literature [35,36], but the number of CMV-DNA copies decreased significantly compared to that in other reports. None of the patients developed CMV disease, whereas Milano F [36] reported an incidence of CMV disease of 5-28%. Sauter C [14] reported that UCBT without ATG was associated with prompt T cell recovery, which might have led to the reduction in CMV infection.…”
Section: Discussionsupporting
confidence: 90%
“…1,6,[17][18][19] The improved immune reconstitution in the group not receiving ATG prior to transplantation was associated with a lower incidence of reactivation of EBV, CMV, and/or adenovirus. Various reports have shown that UCBT recipients are at increased risk of viral reactivation because of the delayed immune recovery, [2][3][4][20][21][22] and early initiation of preemptive antiviral therapy is frequently used to prevent viral disease using a lower cutoff quadruplex DNA value in CB recipients. 5,6,23,24 Although we did not find MAC or RIC regimens to be predictors in this cohort, others have found ATG used in association with RIC regimens to further increase the risk of viral reactivation and specifically the risk of EBV posttransplantation lymphoproliferative disorder (PTLD).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] At our institution, nearly 100% of CMV-seropositive UCBT patients reactivate CMV early posttransplant and require antiviral drug therapy. 17 Previous studies suggest that CMV-specific CD8 1 T cells cannot reliably be detected in UCBT recipients until .100 days after transplant, when thymopoiesis recovers. 14,18 In the few cases where CMV-specific T cells were detected before 100 days, the origin (cord blood or recipient) of these T cells and the breadth of viral antigens recognized were not determined.…”
Section: Introductionmentioning
confidence: 99%